Evolution of aroma compounds in round soy sauce aroma type baijiu during aging and the effect of aging markers on the lasting aroma in finished glass - Shi-Yi Wang; Chen Li; Yu-Jie Li; Guang-Qian Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Song-Tao Wang; Cai-Hong Shen; Xiao-Juan Zhang; Zheng-Hong Xu (Food Chemistry: X)
Soy sauce aroma type Baijiu (SSAB) is a complex blend of seven rounds of raw SSAB, each with distinct aroma profiles that evolve during maturation. Tracking the aging of individual rounds is crucial for understanding flavor development. The round 1–4 SSABs were analyzed by gas chromatography–mass spectrometry and an electronic tongue over one-year aging. Results showed that short/medium-chain esters decrease while long-chain esters, acids, aldehydes, pyrazines, ketones, and furans increase. Kinetic analysis showed that short/medium-chain ethyl esters reach equilibrium in the esterification-hydrolysis reactions, whereas long-chain ethyl esters favor esterification, with their reaction quotient (Qc) diverging from the equilibrium point. Linoleic acid ethyl ester, identified as a key aging marker, was found to reduce the volatilization rate of critical aroma compounds in the finished glass, thereby prolonged the duration of lingering aromas. These findings provide a foundation for improving SSAB blending and storage, highlighting aging's key role in enhancing Baijiu quality.